Method for repairing surface of hammer head of precision forging machine through laser cladding of iron-based composite powder
By using iron-based laser cladding powder to repair the hammer head of the precision forging machine, the problems of complex repair methods and insufficient hardness in the prior art are solved, efficient repair of the hammer head and significant improvement in hardness are achieved, and the service life and reuse rate of the hammer head are significantly improved.
Patent Information
- Application Number
- CN202510418622.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-04-03
- Publication Date
- 2025-05-02
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
In the prior art, when repairing the surface of the hammer head of the fine forging machine, the method of using nickel-based composite coating is complicated. The crack rate between the powder and the substrate is high and it cannot be directly clad. It requires the transition layer and the substrate to be combined before surface clading is carried out. The hardness of the hammer head after repair is insufficient and cannot be used normally.
The hammer head of the finishing machine is repaired by iron-based laser cladding powder. Through pretreatment, flaw detection, selection of suitable laser cladding powder and repair parameter range, laser cladding is carried out multiple times, and finally finishing is carried out to obtain the repaired hammer head.
It significantly improves the service life of the hammer head, improves the repair efficiency, reduces enterprise costs, and improves the reuse rate of used hammer heads. The repaired hammer head hardness reaches 46~52HRC, which is higher than the original hammer head hardness, and significantly enhances the resistance to deformation.
Smart Images

Figure CN119913506A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of metal surface repair, and in particular relates to a method for repairing the surface of a precision forging machine hammer head by laser cladding of iron-based composite powder. Background Art
[0002] At present, the domestic main imports of SKK precision forging machines produced by Austrian GFM company are used to produce and process materials that are difficult to process, such as high-temperature alloys and titanium alloys. The precision forging machine hammer is the main component of the precision forging machine. Figure 1 , Figure 1 The diagram is a diagram of a damaged hammer head of a SKK precision forging machine. During the forging process, multiple symmetrically distributed precision forging hammer heads are simultaneously subjected to high-frequency, high-intensity, and high-impact synchronous forging. In order to improve the performance of the precision forging hammer head, the surface of the imported precision forging hammer head is treated with carburizing, nitriding, spraying, etc. to improve the wear resistance, hardness, fatigue resistance, and impact resistance of the hammer head; however, due to long-term high-intensity forging and impact, the lower surface of the precision forging hammer head is prone to defects such as excessive deformation, abrasion, cracks, pits, and insufficient dimensional accuracy. Figure 2 These defects have a serious impact on high-precision forging of titanium alloys, high-temperature alloys, etc., and are prone to problems such as reduced forging dimensional accuracy, reduced forging efficiency, uneven internal structure of forgings, and increased scrap rate.
[0003] Traditionally, if the imported precision forging machine hammer has defects, it will be scrapped. However, the price of imported precision forging machine hammers is relatively high. A pair of imported precision forging machine hammers costs about 100,000 yuan, and the manufacturing cycle is very long, about 8 months. Directly scrapping will increase the company's economic and time costs, seriously affecting production efficiency. Therefore, repairing the lower surface of the precision forging machine hammer for recycling is an effective way for companies to reduce costs, increase efficiency, and achieve green manufacturing.
[0004] The patent document of the prior art (CN107130238A) proposes a method for repairing the upper surface of the hammer head of a precision forging machine by laser cladding technology. This method laser clads a nickel-based transition alloy layer on the surface of the hammer head of the precision forging machine, and then laser clads a nickel-based surface alloy layer on the transition alloy layer, thereby forming a composite cladding coating on the upper surface of the hammer head. Since this method only repairs the base die steel 56CrNiMoV7 of the hammer head, the preparation method of the nickel-based composite coating used in the repair is complicated, and the powder and the base crack rate are high during the surface cladding, and it is impossible to directly clad. It is necessary to use the transition layer and the base to combine and then perform surface cladding. And because the metal powder of the transition layer and the surface powder of the hammer head have different compositions, they need to be prepared separately, and the cladding process is complicated. According to the records of the patent document, the surface hardness of the hammer head repaired by this method is 23~33HRC, while the technical requirement hardness of the original hammer head is 35~40HRC, HRC is Rockwell hardness. The hammer head repaired by this method is very easy to deform during the forging process and cannot be used normally. Summary of the invention
[0005] In order to solve the above problems existing in the prior art, the present invention provides a method for repairing the surface of a precision forging machine hammer head by laser cladding of iron-based composite powder.
[0006] The technical problem to be solved by the present invention is achieved through the following technical solutions: A method for repairing the surface of a precision forging machine hammer head by laser cladding iron-based composite powder comprises: S100, selecting at least one hammer head with damaged surface of the precision forging machine; S200, performing flaw detection on the at least one hammer head with damaged surface, and determining the hammer head to be repaired according to the flaw detection result; S300, pre-treating the hammer head to be repaired, and then performing trimming processing on the damaged surface of the pre-treated hammer head to obtain a trimmed hammer head; S400, selecting a predetermined laser cladding powder and selecting the optimal repairing method; Complex parameter range; wherein the components of the laser cladding powder include: 0.06-0.08% C, 0.75-0.82% B, 0.91-0.95% Si, 15-18% Cr, 4-5% Ni, 0.3-0.5% Mn, 1-2% Mo and the remainder of Fe; S500, using the laser cladding powder and according to the optimal repair parameter range, performing multiple laser cladding on the hammer head after the trimming process to obtain a laser clad hammer head; S600, fine processing the hammer head after laser cladding to obtain a repaired hammer head.
[0007] 1. The present invention adopts a predetermined iron-based laser cladding powder to repair the hammer head to be repaired once. Compared with the prior art which requires two different cladding repair processes for the transition layer and the surface layer, the service life of the hammer head repaired by the present invention is greatly improved compared with the original hammer head, and the repair efficiency is high, which can quickly solve the bottleneck problem of the traditional repair method, and at the same time significantly improve the problem of the tendency of the hammer head to crack caused by conventional repair powder.
[0008] 2. The present invention uses iron-based laser cladding powder to repair the hammer head. Compared with the prior art using nickel-based powder for repair, the repair cost of the present invention is lower and more environmentally friendly, which can greatly save enterprise costs, increase the reuse rate of waste hammer heads, and significantly improve the economy of the repaired parts.
[0009] 3. The laser cladding method of the present invention has a large applicable thickness for repairing the hammer head surface. The iron-based laser cladding powder and the hammer head substrate made of 56NiCrMoV7 steel have high bonding strength, good density, and a small heat-affected zone, which can effectively avoid substrate deformation and reduce the risk of changes in substrate material properties.
[0010] 4. The laser energy used in the present invention is high, which can make the molten pool exceed the quenching temperature of 56NiCrMoV7 steel, about 800-1000°C, thereby improving the microhardness of the thermal response area; and the hardness of the hammer head after repair is 46-52HRC, which is 35-40HRC higher than the hardness of the original hammer head, the hardness of the bottom surface of the hammer head is significantly improved, and the deformation resistance is significantly enhanced.
[0011] 5. The repair cost of the present invention is low, and the repair cycle is greatly shortened. The repair time of hammer head deformation, wear, cracks, etc. can be completed in two days, saving time cost.
[0012] 6. In the repair process used in the present invention, there is no need to perform heat treatment and preheating treatment on the hammer head substrate before cladding, no transition layer fusion is required during cladding, and no insulation treatment is required for the hammer head after cladding, so the process flow is shortened and the operation is simple.
[0013] The present invention will be further described in detail below with reference to the accompanying drawings and embodiments. BRIEF DESCRIPTION OF THE DRAWINGS
[0014] Figure 1 It is a schematic diagram of the surface damaged hammer head of the SKK type precision forging machine.
[0015] Figure 2 It is a damage diagram of a hammer head with damaged surface.
[0016] Figure 3 The present invention provides a flow chart of a method for repairing the surface of a precision forging machine hammer head by laser cladding of iron-based composite powder.
[0017] Figure 4It is a schematic diagram of the laser cladding provided by the present invention.
[0018] Figure 5 It is a heat-affected zone diagram of the iron-based alloy and the hammer head surface provided by the present invention. DETAILED DESCRIPTION
[0019] The present invention is further described in detail below with reference to specific embodiments, but the embodiments of the present invention are not limited thereto.
[0020] like Figure 3 As shown, the present invention provides a method for repairing the surface of a precision forging machine hammer head by laser cladding iron-based composite powder, comprising: S100, selecting at least one hammer head of the precision forging machine; S200, performing flaw detection on the at least one hammer head, and determining the hammer head to be repaired according to the flaw detection result; S300, pre-treating the hammer head to be repaired, and then performing finishing processing on the damaged surface of the pre-treated hammer head to obtain a finished hammer head; S400, selecting a predetermined laser cladding powder and selecting an optimal repair parameter range; wherein, The components of the laser cladding powder include: 0.06-0.08% C, 0.75-0.82% B, 0.91-0.95% Si, 15-18% Cr, 4-5% Ni, 0.3-0.5% Mn, 1-2% Mo and the balance of Fe; wherein the optimal repair parameter range includes the optimal ranges of powder feeding rate, laser power, scanning speed and overlap rate, corresponding to: 0.3-0.5rad / min, 1600-2000W, 3-5mm / s, 30%-50%. S500, using the laser cladding powder and in accordance with the optimal repair parameter range, the hammer head after trimming is subjected to multiple laser cladding to obtain a hammer head after laser cladding; S600, the hammer head after laser cladding is subjected to fine processing to obtain a repaired hammer head.
[0021] The laser cladding powder of the present invention may be spherical powder with a diameter of 15-45 μm.
[0022] The present invention provides a method for repairing the surface of a precision forging machine hammer head by laser cladding iron-based composite powder, firstly, the surface damaged hammer head is subjected to flaw detection to determine the hammer head to be repaired, then the hammer head is subjected to correction processing, and then it is cleaned and dried; then a predetermined laser cladding powder and an optimal repair parameter range are selected to laser clad the hammer head, and the laser clad hammer head is finely processed to obtain a repaired hammer head. The present invention can keep the structural design of the original hammer head unchanged, and by cladding a layer of iron-based high-temperature alloy repair layer on the surface of the precision forging machine hammer head, a coating effect with dense structure, few microscopic defects, and high metallurgical bonding strength between the cladding layer and the substrate is obtained, and the surface of the hammer head can be repaired for the wear, deformation, pitting and other damaged surfaces, and the repaired hammer head has significantly higher wear resistance and impact resistance than the original hammer head, which reduces the production cost and time cost of the enterprise and effectively improves the production efficiency.
[0023] In a specific embodiment of the present invention, S200 includes: S210, using a cleaning agent to decontaminate and clean the surface of at least one surface-damaged hammer head, and then drying to obtain a dried hammer head; S220, using a penetrant to penetrate the dried hammer head for 10 minutes to obtain a penetrated hammer head; S230, using the cleaning agent to clean the penetrated hammer head to obtain a cleaned hammer head; S240, drying the cleaned hammer head, and then using a developer to develop for 10 minutes to obtain the flaw detection result of the deformed hammer head; S250, according to the flaw detection result, determining the surface-damaged hammer head with a crack less than 4 mm as the hammer head to be repaired.
[0024] The present invention can use the No. 1 special cleaning agent in the colored flaw detection agent to clean the surface of the damaged hammer head, and after drying, use the No. 2 red penetrant to penetrate for 10 minutes, and then use the No. 1 cleaning agent to clean and color. After drying for 3 to 5 minutes, use the No. 3 white developer to develop for 10 minutes. According to the flaw detection treatment result, the crack depth is measured. If the crack depth is greater than 4mm, it cannot be repaired; if the crack is less than 4mm, it can be repaired by laser cladding.
[0025] In a specific embodiment of the present invention, S300 includes: S310, using anhydrous alcohol to clean the hammer head to be repaired, and then drying it in a drying oven to obtain a pretreated hammer head; S320, using a grinder to remove defects and roughen the damaged surface of the pretreated hammer head to obtain a trimmed hammer head.
[0026] In a specific embodiment of the present invention, selecting the optimal repair parameter range in S400 includes: a, designing an orthogonal experimental group, the orthogonal experimental group including four factors and four levels and set values of the four factors within the initial range in each group of experiments; the four factors are: powder feeding rate, laser power, scanning speed and overlap rate; the four levels are the initial ranges corresponding to the four factors; the initial ranges corresponding to the powder feeding rate, laser power, scanning speed and overlap rate are: 0.3-0.9rad / min, 1600-2200W, 3-9mm / s, 30%-60% respectively; b, conducting two orthogonal experiments using the orthogonal experimental group to obtain the optimal repair parameter range.
[0027] This embodiment gradually determines the optimal repair parameter range within a large range, and then can quickly repair the surface of the hammer head to be repaired according to the optimal repair parameter.
[0028] In a specific embodiment of the present invention, b includes: b1, performing an orthogonal experiment according to an orthogonal experiment group, so as to use a laser cladding device to clad the laser cladding powder onto a hammer head sample, a total of 16 times to obtain the first experimental data and the hammer head sample after cladding; b2, cooling the hammer head sample after cladding to room temperature, and then performing a flaw detection experiment and a hardness test to obtain the first flaw detection test result and the first hardness test result; b3, performing a range analysis on both the first flaw detection test result and the first hardness test result, and determining the influence order of the four factors according to the range analysis results; b4, according to the four factors b5, conducting an orthogonal experiment according to the current orthogonal experimental group, so as to utilize laser cladding equipment to clad the laser cladding powder onto a new hammer head sample, a total of 16 times to obtain the second experimental data and the new hammer head sample after cladding; b6, cooling the new hammer head sample after cladding to room temperature, and then conducting a flaw detection experiment and a hardness test to obtain the second flaw detection test result and the second hardness test result; b7, determining the optimal repair parameter range according to the second flaw detection test result and the second hardness test result and using the first experimental data.
[0029] The first flaw detection test result and the first hardness test result are shown in Table 1. The flaw detection test result indicates whether there is a crack.
[0030] Table 1 The first orthogonal test parameters, crack rate and hardness test results
[0031] Refer to Table 2 and Table 3. Table 2 is a table showing the results of crack rate range analysis, and Table 3 is a table showing the results of orthogonal experiment microhardness range analysis.
[0032] Table 2 Crack rate range analysis results of orthogonal experiment
[0033] Table 3 Orthogonal test microhardness range analysis results display table
[0034] K1-K4 in Table 2 and Table 3 are the levels of the four factors. It can be seen from Table 2 that among the four factors affecting the crack rate, the range of laser power is the largest, which is 0.115, followed by scanning speed and powder feeding rate, which are 0.056 and 0.031, and the overlap rate is the smallest, which is only 0.023, which is quite different from the range of laser power, scanning speed and powder feeding rate. This shows that during the cladding process, the overlap rate has little effect on the crack rate. Therefore, when considering the crack rate, the effect of the overlap rate on it is ignored, and priority is given to adjusting the crack rate of the cladding layer by changing the laser power, scanning speed and powder feeding rate. It can be seen from Table 2 that the crack rate shows an increasing trend with the increase of laser power, scanning speed and powder feeding rate. In order to clad a crack-free cladding layer, the laser power, scanning speed and powder feeding rate should be reduced.
[0035] It can be seen from Table 3 that among the four factors affecting microhardness, the range of laser power is the largest, which is 32.075, followed by overlap rate and powder feeding rate, which are 12.475 and 12.225, respectively. The scanning speed is the smallest, which is only 9.40, which is quite different from the range of laser power, overlap rate and scanning speed. This shows that the scanning speed has little effect on the microhardness during the cladding process. Therefore, when considering microhardness, the effect of scanning speed on it is ignored, and priority is given to adjusting the microhardness of the cladding layer by changing the laser power, overlap rate and powder feeding rate. It can be seen from Table 2 that the microhardness shows a trend of increasing first and then decreasing with the increase of laser power, the microhardness shows a trend of increasing first and then maintaining stability with the increase of overlap rate, and the microhardness increases with the increase of powder feeding rate. Since the microhardness shows a trend of increasing first and then maintaining stability with the increase of overlap rate, considering the powder cost, a large overlap rate is excluded.
[0036] Step b4 can adjust the set values of the four factors according to the order of influence of the four factors from large to small. For example, in Table 1, the order of influence of the four factors is laser power, scanning speed, powder feeding rate, and overlap rate. Therefore, the set value of the laser power can be changed first. In order to clad a crack-free cladding layer, assuming that the set value was originally 1800, it can be reduced to 1600, gradually narrowing the range. The same principle applies to other factors. Refer to Table 4, which is a table of the second orthogonal experimental parameters, crack rate and hardness test results.
[0037] Table 4 The second orthogonal test parameters, crack rate and hardness test results
[0038] It can be seen from Table 4 that the crack rate of the new hammer head style after cladding decreases, and the hardness varies under different factors.
[0039] In a specific embodiment of the present invention, b7 includes: b71, determining the first experimental data corresponding to no cracks and a hardness of 46~52HRC based on the second flaw detection test results and the second hardness test results; b72, determining the range composed of the maximum and minimum values in the first experimental data as the optimal repair parameter range.
[0040] In a specific embodiment of the present invention, S500 includes: S510, setting the parameters of the laser cladding equipment according to the optimal repair parameter range; S520, using the laser cladding equipment with set parameters, performing laser cladding twice on the hammer head after the trimming process, and then cooling it to room temperature to obtain the hammer head after laser cladding.
[0041] In a specific embodiment of the present invention, S600 includes: S610, using a 400-800 mesh rough grinding wheel, and setting its spindle speed to 300-600 r / min, leaving a margin of 0.2 mm, and rough grinding the hammer head after laser cladding to obtain a rough-ground hammer head; S620, using an 800-1200 mesh fine grinding wheel, and setting its spindle speed to 600-800 r / min, and fine grinding the rough-ground hammer head to obtain a repaired hammer head.
[0042] In a specific embodiment of the present invention, after S500, the method for repairing the surface of a precision forging machine hammer head by laser cladding iron-based composite powder further includes: testing the hammer head after laser cladding to obtain test results; the test results include the surface hardness of the hammer head after laser cladding and whether there are cracks.
[0043] This step can test the hammer head after laser cladding to test whether there are cracks and whether the surface hardness meets the design requirements. The actual measurement results of the present invention show that the crack rate of the hammer head after laser cladding is less than 0.1%, and the hardness is 46~52HRC, and the original surface hardness of the hammer head is 35~40HRC. The surface hardness of the hammer head after laser cladding of the present invention is higher than the original surface hardness of the hammer head.
[0044] The repair process and repair effect of the present invention are explained below by way of examples.
[0045] Example 1, taking the deformed hammer head (deformation ≤ 1mm) of the SKK type precision forging machine as an example. The deformed hammer head was detected and processed. The flaw detection results showed that the deformation of the deformed hammer head was 0.7mm≤1mm, which met the requirements for repair. The deformed hammer head was ground using a grinder, and a 600-mesh grinding wheel was selected. The spindle speed was 300r / min, so that the surface roughness of the deformed hammer head was Ra=6.4, and the grinding depth was 0.9mm. After grinding, the surface was roughened. The laser cladding powder was selected as an iron-based alloy powder, which was composed of 0.07% C, 0.81% B, 0.95% Si, 18% Cr, 4% Ni, 0.5% Mn, 2% Mo and the rest of Fe. The powder shape was spherical powder with a diameter of 30μm. The surface of the hammer head after the correction process was subjected to multi-pass laser cladding using a semiconductor laser (laser cladding equipment) of model LDF-3000-60. The number of cladding layers was two, the powder feeding rate was 0.3rad / min, and the laser focus position was adjusted at the same time. The spot diameter was 3mm, the laser power was 1650W, the scanning speed was 3mm / s, the overlap rate was 40%, the single-layer cladding height was 1.8mm, the number of cladding passes was 46, and two layers were clad in total. The total height after cladding was 2.8mm; the laser cladding schematic diagram is referenced Figure 4 ,exist Figure 4 The number 1 in the middle is the hammer head substrate to be repaired, and the number 2 represents the laser cladding layer. After cladding, it is naturally cooled to room temperature, and the cladding layer is imaged and inspected. There is no crack on the surface. The surface hardness of the cladding layer is measured with a hardness tester, and the Rockwell hardness value is 48HRC. The surface of the hammer head after cladding is fine-machined until it meets the design tolerance requirements. The fine machining is divided into two steps: rough grinding and fine grinding. A 600-mesh rough grinding wheel is used, the spindle speed is 300r / min, the grinding depth is 1.5mm, and the allowance is 0.4mm. Then a 1200-mesh fine grinding wheel is used, the spindle speed is 800r / min, and the surface roughness after fine grinding is Ra=3.2, and the size meets the technical requirements before repair.
[0046] Example 2, taking the crack hammer head (crack depth ≤ 4mm) of the SKK type precision forging machine as an example. The crack hammer head was subjected to flaw detection, and the flaw detection results showed that the crack depth was 1.9mm≤4mm, which met the requirements for re-repair. The crack was cut using a wire cutting machine, and the cutting groove size was 2.1×81.5×2.0 to remove the oxide layer; then the iron-based alloy powder was selected as the laser cladding powder, which was composed of 0.07%C, 0.81%B, 0.95%Si, 18%Cr, 4%Ni, 0.5%Mn, 2%Mo and the rest of Fe, and the powder shape was spherical powder with a diameter of 30μm; a semiconductor LDF-3000-60 was used. The crack groove was clad with two laser passes by a bulk laser. The number of cladding layers was two, the powder feeding rate was 0.3 rad / min, and the laser focus position was adjusted at the same time. The spot diameter was 3 mm, the laser power was 1900 W, the scanning speed was 3 mm / s, the overlap rate was 30%, the single-layer cladding depth was 1.7 mm, and the total depth of the two-layer cladding was 2.5 mm. After cladding, the hammer head was ground on a grinder, a 600-mesh grinding wheel was selected, and the spindle speed was 300 r / min for grinding, so that the surface roughness Ra=6.4 and the grinding depth was 0.8 mm. The surface was roughened after grinding. The above iron-based powder was selected for secondary cladding of the hammer head. A semiconductor laser of model LDF-3000-60 was used to perform multi-pass laser cladding on the surface of the hammer head. The number of cladding layers was two, the powder feeding rate was 0.5 rad / min, and the laser focus position was adjusted at the same time. The spot diameter was 3 mm, the laser power was 1800 W, the scanning speed was 5 mm / s, the overlap rate was 42%, the single-layer cladding height was 1.8 mm, the number of cladding passes was 46, and two layers were clad in total. The total height after cladding was 2.8 mm; it was naturally cooled to room temperature after cladding; the laser cladding schematic diagram is referenced Figure 4 ,exist Figure 4 1 is the hammer head substrate to be repaired, and 2 is the laser cladding layer. The cladding layer was imaged and tested, and the results showed that there was no crack on the surface. The surface hardness of the hammer head cladding layer was measured using a hardness tester, and the Rockwell hardness value was 49HRC. The surface of the hammer head after cladding was finely processed to meet the design tolerance requirements, divided into two steps: rough grinding and fine grinding. The rough grinding wheel was 600 mesh, the spindle speed was 300r / min, the grinding depth was 1.8mm, and the allowance was 0.3mm. The fine grinding wheel was 1200 mesh, the spindle speed was 800r / min, and the surface roughness after fine grinding was Ra=3.2, and the size reached the technical requirements before repair.
[0047] The prior art patent document (CN107130238A) is to firstly use nickel-based alloy powder to laser-clad a transition alloy layer on the surface of the precision forging machine hammer head, and the nickel-based alloy powder is mixed with 17.5-19% Cr, 10-12.8% Co, 6.3-7.5% Mo, 1-2.6% W, 1.6-2.5% Al, 0.23-0.29% C, 2.1-2.9% Ti, 0.23-0.38% B and the balance Ni, and then laser-clad a surface alloy layer on the surface of the transition alloy layer, and the powder used in the surface alloy layer includes 13-16.8% Mo, 14-18% Cr, 4-5.62% W by mass percentage. , 4.3-5.8% Si, 8.2-9% Fe, and up to 0.15% C, up to 1.2% Mn, up to 0.028% S, up to 0.019% P, up to 2.7% Co, and the rest is Ni. Two powder ratios are required for cladding in two times. The laser power of cladding in the prior art is 2000-2300W. The laser power in the prior art is relatively high, which has a greater impact on the thermal deformation zone of the substrate during cladding. The substrate is prone to deformation and thermal stress concentration. The hardness of the transition alloy layer of the hammer head repaired by the prior art is 20-31HRC, and the hardness of the surface alloy layer is 23-33HRC. The hardness of the transition alloy layer and the surface alloy layer are both lower than the original hardness of the hammer head substrate mold steel 56CrNiMoV7, that is, lower than 35-40HRC, and deformation and other problems are prone to occur in actual forging.
[0048] The present invention uses an iron-based laser cladding powder mixed with 10.06-0.08% C, 0.75-0.82% B, 0.91-0.95% Si, 15-18% Cr, 4-5% Ni, 0.3-0.5% Mn, 1-2% Mo and the remainder of Fe to complete the process; the reason for the transition layer cladding used in the prior art is mainly because the surface cladding powder is directly clad on the substrate and the crack rate is very high, so the transition layer cladding is required for combined cladding. The iron-based powder cladding of the present invention only requires one cladding process to achieve a crack-free cladding layer, and the crack tendency rate is very low; the hardness of the hammer head repaired by the present invention is 46-52HRC, which is higher than the original hardness of the hammer head, and the service life is significantly increased in actual production. The repaired hammer head of the present invention has been verified and applied in actual production. Four precision forging machine hammer heads were installed on an SKK type 100-ton precision forging machine. At a forging frequency of 900 times / min, titanium alloy round bars with a size of Φ90×3000mm were forged. The number of forged bars was increased to 100 compared with the original hammer head, and there was basically no crack on the working surface.
[0049] refer to Figure 5 , Figure 5 This is the heat affected zone diagram of the iron-based laser cladding powder cladding and the hammer head surface. Figure 5It can be seen that compared with other methods for repairing the hammer head surface, the laser cladding method used in the present invention has a large applicable thickness for repairing the hammer head surface, and the clad iron-based laser cladding powder and the substrate 56NiCrMoV7 steel have high bonding strength, good density, and a small heat-affected zone, which can effectively avoid substrate deformation and reduce the risk of changes in substrate material properties.
[0050] In practical applications, a universal tension / compression testing machine (10 tons) was used to carry out tension and compression tests, and the results are shown in Table 5.
[0051] Table 5 Compression strength analysis of hammer head repaired by iron-based laser cladding powder
[0052] The results in Table 5 show that the compressive strength of the hammer head clad with the iron-based laser cladding powder of the present invention is significantly higher than that of the original hammer head.
[0053] In addition, the terms "first" and "second" are used for descriptive purposes only and should not be understood as indicating or implying relative importance or implicitly indicating the number of the indicated technical features. Therefore, the features defined as "first" and "second" may explicitly or implicitly include one or more of the features. In the description of the present invention, the meaning of "plurality" is two or more, unless otherwise clearly and specifically defined.
[0054] Although the present application is described herein in conjunction with various embodiments, in the process of implementing the present application for which protection is claimed, those skilled in the art may understand and implement other variations of the disclosed embodiments by reviewing the drawings, the disclosure, and the appended claims. In the claims, the word "comprising" does not exclude other components or steps, and "a" or "an" does not exclude a plurality of components or steps.
[0055] The above contents are further detailed descriptions of the present invention in combination with specific preferred embodiments, and it cannot be determined that the specific implementation of the present invention is limited to these descriptions. For ordinary technicians in the technical field to which the present invention belongs, several simple deductions or substitutions can be made without departing from the concept of the present invention, which should be regarded as falling within the protection scope of the present invention.
Claims
1. A method for repairing the surface of a precision forging machine hammer head by laser cladding of iron-based composite powder, characterized in that: include: S100, selecting at least one hammer head with damaged surface of a precision forging machine; S200, performing a flaw detection process on the at least one hammer head with damaged surface, and determining a hammer head to be repaired according to the flaw detection process result; S300, pre-treating the hammer head to be repaired, and then trimming the damaged surface of the pre-treated hammer head to obtain a trimmed hammer head; S400, selecting a predetermined laser cladding powder and selecting an optimal repair parameter range; wherein the components of the laser cladding powder include: 0.06-0.08% C, 0.75-0.82% B, 0.91-0.95% Si, 15-18% Cr, 4-5% Ni, 0.3-0.5% Mn, 1-2% Mo and the balance Fe; the optimal repair parameter range includes the optimal range of powder feeding rate, laser power, scanning speed and overlap rate, corresponding to: 0.3-0.5 rad / min, 1600-2000 W, 3-5 mm / s, 30%-50%; S500, using the laser cladding powder and according to the optimal repair parameter range, performing laser cladding on the hammer head after the trimming process for multiple times to obtain a laser clad hammer head; S600, finishing the hammer head after laser cladding to obtain a repaired hammer head.
2. The method for repairing the surface of a precision forging machine hammer head by laser cladding iron-based composite powder according to claim 1 is characterized in that: S200 includes: S210, using a cleaning agent to clean and decontaminate the surface of the at least one hammer head with damaged surface, and then drying the hammer head to obtain a dried hammer head; S220, penetrating the dried hammer head with a penetrant for 10 minutes to obtain a penetrating hammer head; S230, using the cleaning agent to clean the infiltrated hammer head to obtain a cleaned hammer head; S240, drying the cleaned hammer head, and then developing the hammer head with a developer for 10 minutes to obtain a flaw detection result of the deformed hammer head; S250, according to the flaw detection result, determining the surface damaged hammer head with a crack smaller than 4 mm as the hammer head to be repaired.
3. The method for repairing the surface of a precision forging machine hammer head by laser cladding iron-based composite powder according to claim 1 is characterized in that: S300 includes: S310, cleaning the hammer head to be repaired with anhydrous alcohol, and then drying it in a drying oven to obtain a pretreated hammer head; S320, using a grinder to remove defects and roughen the damaged surface of the pre-treated hammer head to obtain a trimmed hammer head.
4. The method for repairing the surface of a precision forging machine hammer head by laser cladding iron-based composite powder according to claim 1, characterized in that: The optimal repair parameter range selected in S400 includes: a. Design an orthogonal experimental group, wherein the orthogonal experimental group includes four factors and four levels and the set values of the four factors within the initial range in each experiment; the four factors are: powder feeding rate, laser power, scanning speed and overlap rate; the four levels are the initial ranges corresponding to the four factors; the initial ranges corresponding to the powder feeding rate, the laser power, the scanning speed and the overlap rate are: 0.3-0.9rad / min, 1600-2200W, 3-9mm / s, 30%-60% respectively; b. Perform two orthogonal experiments using the orthogonal experimental group to obtain the optimal repair parameter range.
5. The method for repairing the surface of a precision forging machine hammer head by laser cladding of iron-based composite powder according to claim 4, characterized in that b include: b1, an orthogonal experiment is performed according to the orthogonal experimental group to use the laser cladding equipment to clad the laser cladding powder onto the hammer head sample, a total of 16 times to obtain the first experimental data and the hammer head sample after cladding; b2, cooling the clad hammer head sample to room temperature, and then performing a flaw detection test and a hardness test to obtain a first flaw detection test result and a first hardness test result; b3, perform range analysis on the first flaw detection test results and the first hardness test results, and determine the influence order of the four factors based on the range analysis results; b4, adjusting the set values of the four factors according to the influence order of the four factors to obtain the current orthogonal experimental group; b5, performing an orthogonal experiment according to the current orthogonal experimental group, so as to use the laser cladding equipment to clad the laser cladding powder onto the new hammer head sample, a total of 16 times to obtain the second experimental data and the new hammer head sample after cladding; b6, cooling the new hammer head sample after cladding to room temperature, and then performing a flaw detection test and a hardness test to obtain a second flaw detection test result and a second hardness test result; b7. Determine the optimal repair parameter range based on the second flaw detection test results and the second hardness test results and by using the first experimental data.
6. The method for repairing the surface of a precision forging machine hammer head by laser cladding iron-based composite powder according to claim 5, characterized in that: b7 includes: b71, according to the second flaw detection test results and the second hardness test results, determine the first experimental data corresponding to no cracks and hardness of 46~52HRC; b72, determining the range consisting of the maximum value and the minimum value in the first experimental data as the optimal repair parameter range.
7. The method for repairing the surface of a precision forging machine hammer head by laser cladding of iron-based composite powder according to claim 1, characterized in that: S500 includes: S510, setting parameters of the laser cladding equipment according to the optimal repair parameter range; S520, using a laser cladding device with set parameters, laser cladding the trimmed hammer head twice, and then cooling it to room temperature to obtain a laser clad hammer head.
8. The method for repairing the surface of a precision forging machine hammer head by laser cladding of iron-based composite powder according to claim 1, characterized in that: S600 includes: S610, using a 400-800 mesh rough grinding wheel, setting its spindle speed to 300-600 r / min, leaving a margin of 0.2 mm, and rough grinding the hammer head after laser cladding to obtain a rough-ground hammer head; S620, using a fine grinding wheel with a mesh of 800-1200 and setting its spindle speed to 600-800 r / min, fine grinding the roughly ground hammer head to obtain a repaired hammer head.
9. The method for repairing the surface of a precision forging machine hammer head by laser cladding of iron-based composite powder according to claim 1, characterized in that: After S500, the method for repairing the surface of a precision forging machine hammer head by laser cladding iron-based composite powder further includes: The hammer head after laser cladding is tested to obtain test results; the test results include the surface hardness of the hammer head after laser cladding and whether there are cracks.
Citation Information
Patent Citations
Method for recovering hammer of refined forging machine through laser cladding
CN107130238A
Laser cladding material and train rail laser cladding repair process
CN112281082A
Welding wire for precision forging machine hammerhead surfacing and precision forging machine hammerhead surfacing method
CN112570926A
Iron-based alloy powder and method for producing molded body
WO2024058145A1
Cited By
Clutch driving shaft platform additive repairing method based on laser cladding technology
CN120325992A